EOR SCREENING AND OPTIMIZING STUDY ON SANDSTONE RESERVOIRS - MOHIYADDIN, MUHAMMAD ZAKI (Universiti Teknologi PETRONAS, 2011)
C02 flooding is often applied as the tettiacy recovery technique for light and meditifil oils after water flooding. Water flooding leaves high water saturation inside the reservoir. As a resuit, the reservoir fluid system consists of hydrocarbon and high water saturation. Therefore, for the C02 based EOR techniques, knowledge of multiphase behaviour and properties of C02 -reservoir fluids (hydrocarbon and water) mixture is important in order to determine the displacement efficiency, recovery evaluation, development, design and operation of the process. It has been suggested that the high recovery of C02 flooding above certain pressure is a result of the formation of a dense C02 liquid phase that efficiently extract the C5+ fraction of the oil. From the C02 properties studies, C02 is in liquid phase when the temperature is under its critical temperature (31.1 °C) and at certain pressure range. This study aims to investigate the phase behaviour of C02, hydrocarbon and high water content under low temperature (60°C to 30°C), so that we can predict the phases that is present and estimate the volume percentage of the phases. This J!fOject consists of experimental work to predict the phase behaviour of two samples. The first sample is C02 and Dulang oil mixture (as the base case) and the second sample is C02, Dulang oil and water mixture. The temperature of wax formation is identified and the volume phases are measured at different low temperatures range (30°C to 60°C) and pressures of 2500psi to 500psi. The viscosity of C02 and hydrocarbon mixture is measured as additional properties analysis. Results of the experiments show that, gas, C02-rich liquid and oil-rich liquid (G/L1/Lz) occurred for COz-Crude oil mixtures at temperature below the C02 critical temperature (31 °C) and at the pressure of around 900 psi. From compositional analysis, the C02-rich liquid phase (L2) that occurred is resulted from the extracted C5+ component of the oil. This indicates that C02 can achieve miscibility with Dulang oil at temperature of 30°C. While for the C02, Dulang oil and water mixture, no formation of C02-rich liquid phase occurred. This may be due to the solubility of C02 in the water, leaving only little volume of C02 to react with the oil.